2012
DOI: 10.4236/fns.2012.34074
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Varied Dietary Crude Protein Levels with Balanced Amino Acids on Performance and Egg Quality Characteristics of Layers at First Laying Phase

Abstract: Four diets were formulated to study the influence of varying crude protein levels on the performance, egg quality, serum and haematological characteristics at the first phase of laying cycle of sixty Bovan Nera laying birds that were randomly allotted to dietary treatments. The four experimental diets had five replicates each and three birds per replicate. Diet 1 contained 14% crude protein (CP), while diet 2 contained 15% CP, diets 3 and 4 contained 16% and 17% CP respectively. The experimental birds were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 8 publications
2
14
0
1
Order By: Relevance
“…According to Jardim Filho et al (2008), failure in nutrient supply results in poor quality eggs before impairment in the mobilization of nutrients for the maintenance of the reproductive system and the process of egg formation. This is particularly true when it comes to protein levels which determine production costs and depression of performance parameters and egg quality (ADEYEMO et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to Jardim Filho et al (2008), failure in nutrient supply results in poor quality eggs before impairment in the mobilization of nutrients for the maintenance of the reproductive system and the process of egg formation. This is particularly true when it comes to protein levels which determine production costs and depression of performance parameters and egg quality (ADEYEMO et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to Alagawany et al (2016), the live body weight of laying hens improved in the hens supplemented with high levels (18% and 20 % CP) as to low protein diets (12%, 14%, and 16%). Similarly, Adeyemo et al (2012) reported that higher levels of dietary protein lead to increases in egg production and egg weight, which resulted significant improvement in the feed to egg mass ratio. However, the result is contrary to the findings of Kingori et al (2010) who reported the body weight of laying hens was not affected by dietary protein level.…”
Section: Discussionmentioning
confidence: 95%
“…This is in agreement with the study of de Beer and Coon (2006) that hens fed high protein had higher egg production. Research of Adeyemo et al (2012) indicated that there were a direct relationship between protein intake and performance of laying hen at the first production. Joseph et al (2000) suggested that the high protein level in feed result high egg production.…”
Section: Egg Production and Egg Weightmentioning
confidence: 99%